No Association Between Loneliness, Episodic Memory and Hippocampal Volume Change in Young and Healthy Older Adults: A Longitudinal European Multicenter Study - Solé-Padullés, Cristina; Macià, Dídac; Andersson, Micael; Stiernstedt, Mikael; Pudas, Sara; Düzel, Sandra; Zsoldos, Enikő; Ebmeier, Klaus P.; Binnewies, Julia; Drevon, Christian A.; Brandmaier, Andreas M.; Mowinckel, Athanasia M.; et al. (Frontiers in Aging Neuroscience, 2022)
Background: Loneliness is most prevalent during adolescence and late life and has been associated with mental health disorders as well as with cognitive decline during aging. Associations between longitudinal measures of loneliness and verbal episodic memory and brain structure should thus be investigated. Methods: We sought to determine associations between loneliness and verbal episodic memory as well as loneliness and hippocampal volume trajectories across three longitudinal cohorts within the Lifebrain Consortium, including children, adolescents (N=69, age range 10-15 at baseline examination) and older adults (N=1468 over 60). We also explored putative loneliness correlates of cortical thinning across the entire cortical mantle. Results: Loneliness was associated with worsening of verbal episodic memory in one cohort of older adults. Specifically, reporting medium to high levels of loneliness over time was related to significantly increased memory loss at follow-up examinations. The significance of the loneliness-memory change association was lost when eight participants were excluded after having developed dementia in any of the subsequent follow-up assessments. No significant structural brain correlates of loneliness were found, neither hippocampal volume change nor cortical thinning. Conclusions: In the present longitudinal European multicenter study, the association between loneliness and episodic memory was mainly driven by individuals exhibiting progressive cognitive decline, which reinforces previous findings associating loneliness with cognitive impairment and dementia.